Literatur Review: Pengaruh Lingkungan Keluarga Terhadap Kemampuan Berbahasa Siswa di Sekolah Dasar (SD) - Arhaya Umil Azmah; Dea Melfiana Putri; Adrias Adrias; Fadila Suciana (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
The family is the first and foremost environment that provides children with social and linguistic experiences. Parents and other family members serve as the child's first language model, significantly influencing their language development in the future. This literature study aims to analyze the impact of the family environment on the language skills of elementary school students. The study employs a literature review method by referencing previous research journals relevant to the topic.Through journal searches, five relevant studies were identified. The majority of these studies applied a descriptive method design with a qualitative approach, while some also incorporated ex-post facto quantitative methods. Despite variations in research findings, all studies consistently indicate that the family environment plays a crucial role in shaping children's language skills. Factors such as parental involvement, the frequency of verbal interactions at home, and the availability of reading materials contribute significantly to children's linguistic development. Additionally, supportive family environments, where parents actively engage in conversations and storytelling, positively impact children's vocabulary acquisition and reading abilities.Based on the literature review results, it can be concluded that the family environment influences children's language skills. While the findings of each study may differ, they share a common conclusion regarding the significance of family interactions in shaping children's reading and communication abilities. These findings highlight the importance of fostering a language-rich home environment to support children's linguistic growth. Future research is suggested to further explore strategies that enhance parental involvement in children's language development.